2014
DOI: 10.1037/a0034581
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration and recovery of DAP IQ scores in the repeated assessment of the Naglieri Draw-A-Person (DAP) test in 6- to 12-year-old children.

Abstract: The study investigated whether mental age in children, as assessed by the IQ in the Draw-A-Person (DAP) test (Naglieri, 1988), can be improved by practice. In addition, it was tested whether children needed novel content to keep up their performance level during test repetition. The DAP test was given to 6-, 8-, 10-, and 12-year-old children (N ϭ 80) 3 times. In addition, they drew a police figure 2 times, with task sequence counterbalanced. Repeated drawings resulted in significant omission of detail and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 79 publications
(79 reference statements)
4
17
2
Order By: Relevance
“…Novelty is assumed to have an important wake-up and refresher function that increases mental alertness (Lange-Küttner et al, 2014;Luchins, 1942Luchins, , 1950, while repetition increases familiarity in order to strengthen and consolidate memory traces (Ebbinghaus, 1964;Lange-Küttner, 2011). It was not obvious to participants that the objects-in-places were repeated because trials were presented in a randomized sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novelty is assumed to have an important wake-up and refresher function that increases mental alertness (Lange-Küttner et al, 2014;Luchins, 1942Luchins, , 1950, while repetition increases familiarity in order to strengthen and consolidate memory traces (Ebbinghaus, 1964;Lange-Küttner, 2011). It was not obvious to participants that the objects-in-places were repeated because trials were presented in a randomized sequence.…”
Section: Discussionmentioning
confidence: 99%
“…School-aged children tend to loose details in repetitive productive tasks (Lange-Küttner, Küttner, & Chromekova, 2014), just like adults loose detail when they extract the gist of a narrative in their episodic memories (Bartlett, 1932). Furthermore, visual or motoric re-visiting of object locations that were inspected before leads to inefficient place memory (Danziger, Kingstone, & Snyder, 1998;Klein, 1988;Posner, Rafal, Choate, & Vaughan, 1985).…”
Section: Repetition Versus Perseverationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliability of the DAP:IQ may be negatively affected by fatigue when the task is completed repeatedly [21]. Recently, a large twin study [2] found that drawing performance and intelligence are both heritable, and found a relationship between DAP task performance at age four and intelligence 1Inter-rater reliability on the DAP:IQ reported by [40] was r = 0.83, whereas the test developers [30] report inter-rater reliability measures of r = .95 for drawings by older children and adults (age range 11-75), and r = .91 for younger children (age range [6][7][8][9][10][11] at age fourteen, ten years later.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, only older children would attend less to surface details. Hence, we concluded that girls-like in human figure drawings [33,[35][36][37]-were drawing more detail. However, different to the human figure drawings where girls excel in detail, the details of the cubes had no names, still they would embark on laboriously drawing details in this cube drawing task.…”
Section: Girls In Detail Boys In Shapementioning
confidence: 82%